Analisa Defect pada Produk Back Cover Menggunakan Metode PDCA untuk Pengurangan Claim Customer di PT. XYZ - Trianda, Fajar; Wiyatno, Tri Ngudi; Kustiwan, Susan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
XYZ is a manufacturing company that produces television back cover components and is required to meet customer quality standards. However, in April, a defect rate of 7% was found, exceeding the company's tolerance limit of 5%, with the dominant type of defect being dirty defects. This situation has led to an increase in customer claims and has affected both quality costs and the company's reputation. This study aims to analyze the causes of dominant defects in back cover products and formulate corrective actions to reduce customer claims using the Plan Do Check Action (PDCA) method. The research method used is quantitative descriptive with data collection techniques through observation, interviews, and production data analysis. Analytical tools include check sheets, Pareto diagrams, fishbone diagrams, and 5W+1H analysis. Research results indicate that the implementation of PDCA is able to identify the root causes of defects and generate effective improvement proposals to reduce defect levels and continuously enhance product quality.